2017
DOI: 10.1016/j.rbre.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rheumatoid arthritis in the public health system in Santa Catarina, Brazil: a descriptive and temporal trend analysis from 1996 to 2009

Abstract: During the observed period, a reduction in the number of hospital admissions for both clinical and orthopedic surgical procedures related to this disease was observed. Nevertheless, there was an increase in the cost of medical admissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…The first restriction refers to the number of RA patients treated by the SUS with biologic medicines. These studies [48,50,56] record data from 1996 facilitated by the MoHB (only 10% of RA patients used biological medicines). The second concerns access in the medicines availability dimension: the restriction rate adopted was 50%, based on published studies and other sources between 1998 and 2005 [57][58][59][60].…”
Section: Values Determined With the Modeled Calculation Of The Budget...mentioning
confidence: 99%
“…The first restriction refers to the number of RA patients treated by the SUS with biologic medicines. These studies [48,50,56] record data from 1996 facilitated by the MoHB (only 10% of RA patients used biological medicines). The second concerns access in the medicines availability dimension: the restriction rate adopted was 50%, based on published studies and other sources between 1998 and 2005 [57][58][59][60].…”
Section: Values Determined With the Modeled Calculation Of The Budget...mentioning
confidence: 99%
“…Brazilian Journal of Development, Curitiba, v.7, n.9, p. 91805-91819 sep. 2021 Dentre estas doenças a artrite reumatoide tem merecido mais atenção pelas consequências que podem causar ao paciente senão tratada corretamente (GOMES, 2017).…”
Section: Introductionunclassified
“…In iximab, administered intravenously, was the rst available TNFα inhibitor, and its bene ts in IMID management are well established. National studies performed using administrative databases that document direct expenses for outpatient and drug treatment of autoimmune diseases indicated that medications accounted for 68.72% of the total medical expenditure in patients with rheumatoid arthritis, with the most prescribed biologic medication being in iximab [3]. In Brazil, free access to in iximab is regulated through the Specialized Component of Pharmaceutical Assistance, a strategy to allow access to medicines within the scope of the Uni ed Health System that seeks to guarantee the completeness of treatments at the outpatient level through lines of care de ned in the Clinical Protocols and Therapeutic Guidelines published by the Ministry of Health [4].…”
mentioning
confidence: 99%